Decoupling between chain extension and entanglement via branched structures for ultralow-power biaxially stretched polypropylene capacitor films - Qi Wu; Can Zhao; Enhui Liu; Xuan Wang; Jing Zhou; Rui Han; Min Nie (Chemical Engineering Journal, 2026)

2-Hydroxyfluorene triggers a vicious cycle of oxidative stress and gut dysbiosis, leading to intestinal injury in the polychaete Perinereis aibuhitensis - Enhui Liu; Yining Huang; Ziqiao Zhao; Teng Teng; Honglei Zhou; Chune Liu; Feng Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

MnO₂ polymorphs direct the selective degradation of fluoroquinolone antibiotics: Insights from adsorption, oxidation, and O₂ activation mechanisms - Ruohan Zhao; Enhui Wu; Xiangyu Zhu; Xinfei Ge; Xin Xiao; Baoliang Chen (Chemical Engineering Journal, 2026)

A novel forest fire scenario deduction method based on belief rule base - Rui Zhao; Ning Wang; Wenguang Yan; Enhui Zhao (Natural Hazards, 2026)

A novel river pattern classification rule based on geometric parameters of channel planform - Zhou Yang; Enhui Jiang; Yanhui Liu; Yuanjian Wang; Wanjie Zhao; Gang Liu (CATENA, 2026)

Photoreactive bromide ions as overlooked regulators of nanoplastic surface chemistry and aggregation in sunlit seawater - Xinjie Wang; Enhui Jiang; Yining Wang; Jian Zhao; Shuang Xu; Xinghui Xia; Yang Li (Water Research, 2026)

Adipocytes as core drivers of skin aging and novel targets for regeneration - Enhui Wang; Zijun Xu; Yuting Wang; Junbo Wang; Yanfei Jiang; Chunyue Zhao (Biogerontology, 2026)

Strengthening coordination for electrolyte diluent via dipole polarization enables rapid Na+ solvation/desolvation kinetics - Yan Meng; Yuanheng Wang; Qingjiang Liu; Xingyu Chen; Enhui Wang; Weihua Chen; Hongji Pan; Jinghao Zhao; Xin Li; Jia-Yan Liang (Chemical Engineering Journal, 2025)

A review of weed image identification based on deep few-shot learning - Enhui Wu; Yu Chen; Ruijun Ma; Xiande Zhao (Computers and Electronics in Agriculture, 2025)

A multi-attribute decision-making method of cascade reservoir joint scheduling schemes considering water–sediment, eco-environment, and socio-economy in the Yellow River Basin - Donglin Li; Jieyu Li; Yuanjian Wang; Enhui Jiang; Wanjie Zhao; Gang Liu; Zhifeng Yang (Journal of Hydrology, 2025)

Annual multi-objective optimization model and strategy for scheduling cascade reservoirs on the Yellow River mainstream - Gang Liu; Enhui Jiang; Donglin Li; Jieyu Li; Yuanjian Wang; Wanjie Zhao; Zhou Yang (Journal of Hydrology, 2025)

Diversity Analysis of Microbial Communities in Shrimp Polyculture Ponds in Coastal Saline–Alkali Regions of Hebei, China - Enhui Suo; Zhao Chen; Huan Gao; Shijia Yuan; Zhiqiang Chang (Fishes, 2025)
To investigate the structure and successional dynamics of microbial communities in shrimp culture ponds in coastal saline–alkali regions of Hebei, China, we compared the water microbiota of Litopenaeus vannamei monoculture ponds and L. vannamei–Macrobrachium rosenbergii polyculture ponds in the early, mid, and late culture stages. The results revealed clear temporal succession patterns in both the diversity and composition of microeukaryotic and bacterial communities. Distinct differences were also observed between the two culture models. Compared with monoculture, polyculture ponds showed 2.23–34.76% lower abundances of parasitic microeukaryotes, such as Rozellomycota and Perkinsida. In contrast, the abundances of carbon- and nitrogen-cycling bacterial groups (e.g., LD29, CL500-29_marine_group) and Chlorophyta were 0.24–50.94% higher in the polyculture system. Co-occurrence network analysis showed that polyculture enhanced competitive interactions and increased the network structural complexity within bacterial and cross-domain microbial networks. These findings help elucidate the mechanisms underlying efficient shrimp production in saline–alkali ponds and support the optimization of aquaculture models.

Biological properties, synthetic pathways and anti-aging mechanisms of nicotinamide mononucleotide (NMN): Research progress and challenges - Enhui Wang; Yuting Wang; Zhaofeng Zhang; Yanfei Jiang; Chunyue Zhao (Biogerontology, 2025)

K-modified cyano-rich carbon nitride for photocatalytic production of water treatment agent - Hydrogen peroxide in two-phase system - Yanhe Li; Zelin Ma; Yi Yang; Xia Li; Enhui Gao; Qiming Zhao; Xiao Chen; Hao Zhang (Journal of Water Process Engineering, 2025)

Multiscale modelling and simulation of coal separation process in a pilot-scale gas–solid fluidized bed - Ying Jia; Yong Zhang; Wei Han; Xianqiang Xiong; Enhui Zhou; Ji Xu; Chenlong Duan; Yuqing Feng; Yuemin Zhao; Wei Ge (Chemical Engineering Journal, 2025)

Spatial confinement of Co-N/O nanocatalyst into hollow carbon nanosphere for water purification and its biotoxicity assessment - Chen Fang; Yangyang Bai; Lingyuan Ma; Yejun Pan; Kun Pang; Jiaying Yan; Jiajun Song; Enhui Jiang; Haiyu Zhao; Chuanying Pan; Xiang Liu; Xianyong Lan (Chemical Engineering Journal, 2025)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

A Comparative Study of the Effects of Extrusion on Lignocellulose Structure and Biogas Production from Wheat Straw and Digested Wheat Straw - Guangyin Chen; Hainan Cao; Changping Zhao; Wanrong Zhang; Jiawei Zheng; Enhui Wang (BioEnergy Research, 2023)

Agglomeration behavior of the dense medium in a gas–solid separation fluidized bed - Yadong Zhang; Yani Dong; Guannan Lv; Liang Dong; Yuemin Zhao; Chenlong Duan; Enhui Zhou; Wei Hua (Fuel, 2023)

The contribution of earthworms to carbon mineralization during vermicomposting of maize stover and cow dung - Yuxiang Chen; Yan Zhang; Xiong Shi; Enhui Shi; Tingting Zhao; Yi Zhang; Lixin Xu (Bioresource Technology, 2023)

ENSO and PDO-related interannual and interdecadal variations in the wintertime sea surface temperature in a typical subtropical strait - Yimin Zhang; Zhonghua Zhao; Enhui Liao; Yuwu Jiang (Climate Dynamics, 2022)

The non-negligibility of greenhouse gas emission from a combined pre-composting and vermicomposting system with maize stover and cow dung - Lei Zhang; Tingting Zhao; Enhui Shi; Zunhao Zhang; Yan Zhang; Yuxiang Chen (Environmental Science and Pollution Research, 2021)